Pembelajaran Berbasis Projek (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Early Childhood Education learning will be more meaningful if the learning is carried out using projects, and an introduction to concrete objects, so that children in the foundation phase get meaningful learning, and will give them valuable experience while studying at school. This is related by giving them the right to exercise independence in learning and giving them space to explore the experiences they are facing, one of which is by carrying out or creating projects that will make their survival more meaningful than just getting material in the form of content. The hope here is that the project will help children gain a learning style that is fun and meaningful and can increase their understanding of the world challenges they face today.